Spiraea decumbens Koch subsp. tomentosa (Poech) Dostál (Spiraea hacquetii Fenzl & K. Koch), novelty for the flora of Slovenia and the Dinaric Alps - Dakskobler, Igor (Hacquetia, 2023)
In Govci under Mt. Poldanovec above the Trebuša Valley we found a new locality of southeastern-Alpine endemic Spiraea decumbens subsp. tomentosa, which is new to the flora of Slovenia and the Dinaric Alps. Its closest known localities are in the western Julian Prealps in Northeastern Italy. A small population of several ten shrublets occurs at elevations of about 570 m in shady, almost vertical dolomite rocks, in a stand of the endemic association Phyteumato columnae-Primuletum carniolicae. Despite a very small population we assume there are other localities in this area, where numerous gorges are very difficult to reach and have therefore not yet been sufficiently studied.